Prenatal diagnosis of a maternal 7.22-Mb deletion at chromosome 4q32.2q32.3 by SNP array - Zhang, Pingping (Mol Cytogenet, 2020)
BACKGROUND: Although Chromosomal microarray analysis (CMA) is a powerful diagnostic technology for detecting chromosomal copy number variants (CNVs), it detects numerous variants of unknown significance (VUSs), which poses a great challenge for genetic counselling. Terminal deletion of the long arm of chromosome 4 is a rare genetic aberration. Few cases of interstitial deletion sharing the common deleted segment have been reported. CASE PRESENTATION: A male foetus with a 7.22-Mb deletion at chromosome 4q32.2q32.3 was found in the proband. The paternal genotype was normal. His asymptomatic mother with a normal phenotype and intelligence was found to carry the same deletion at the long arm of chromosome 4. The clinical significance of arr[GRCh37] 4q32.2q32.3(162858958_170081268)×1 remains uncertain. To the best of our knowledge, this is the first case report on a VUS of 4q32 deletion and the second report of a heterochromatic CNV involving part of the long arm of chromosome 4 in a phenotypically normal mother and child. The identification of this case contributes to additional understanding of deletion at 4q32.2q32.3. This report may provide a reference for prenatal diagnosis and genetic counselling in patients who have genotypes of similar cytogenetic abnormalities. CONCLUSIONS: The novel 7.22-Mb deletion at chromosome 4q32.2q32.3 (162858958-170081268) is a VUS. The foetus inherited this VUS from a phenotypically normal mother.